Unmet Cardiac Clinical Needs in Adult Mucopolysaccharidoses - Stepien, Karolina M.; Braunlin, Elizabeth A. (Frontiers in Cardiovascular Medicine, 2022)
The Mucopolysaccharidoses (MPSs) are a group of heterogenous disorders with complex multisystemic presentations. Although Haematopoietic Cell Transplantation (HCT) and Enzyme Replacement Therapy (ERT) have extended the lifespan of individuals affected with MPS well into adulthood, reversal of pre-existing cardiac, skeletal and neurocognitive deficits does not occur, so there are no truly curative treatments available to these patients at present. The medical and surgical management of cardiovascular problems in adults with MPS is complicated by these pre-existing comorbidities, requiring the involvement of multidisciplinary and multispecialty perioperative teams. This review sets out to describe the unmet cardiac needs in adults with MPS disorders including the lack of effective treatments, monitoring guidelines, and the challenges regarding expertise and training, and psychosocial support.